2012
DOI: 10.4315/0362-028x.jfp-11-196
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Methods To Prepare Samples of Leafy Green Vegetables for Preenrichment with the Bacteriological Analytical Manual Salmonella Culture Method

Abstract: Three sample preparation procedures, soak, stomach, and blend, were evaluated using the Bacteriological Analytical Manual Salmonella culture method with eight types of leafy green produce. In the soak method, test portions were added to lactose broth without homogenization; in the stomach method, test portions were stomached with lactose broth; and in the blend method, test portions were blended with lactose broth. Twenty artificially contaminated test portions were analyzed with each procedure in indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…However, in this case tissue samples were inoculated in the laboratory with 10 CFU/sample of either PTVS177 or PTVS155 that were directly applied to the plant material contained in sterile bags. Inoculated material was stored at 5 C for 16e18 h before enrichment in order to pre-condition the cells to a lower metabolic activity (Jacobson et al, 2012;Kase et al, 2012).…”
Section: Description Of the Field Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in this case tissue samples were inoculated in the laboratory with 10 CFU/sample of either PTVS177 or PTVS155 that were directly applied to the plant material contained in sterile bags. Inoculated material was stored at 5 C for 16e18 h before enrichment in order to pre-condition the cells to a lower metabolic activity (Jacobson et al, 2012;Kase et al, 2012).…”
Section: Description Of the Field Trialmentioning
confidence: 99%
“…These challenges involve the inability of differentiating viable from dead cells, without significant additional sample processing, or those cells that can be in a viable but not culturable physiological condition (VBNC) (Moyne, Harris, & Marco, 2013). Furthermore, there may be substantial interference, difficult to predict in a nonvalidated matrix, of plant or food components that can cause inhibition of the PCR reaction (Harris & Griffiths, 1992;Jacobson, Gill, Irvin, Wang, & Hammack, 2012;Kim et al, 2012;Taskila, Toumola, & Ojamo, 2012). Commonly, low numbers of cells are present on contaminated samples that, alone, make detection difficult, but cells can also be sub-lethally injured or stressed which may delay recovery and reaching the critical detection threshold during an enrichment step (Havelaar et al, 2010;Kisluk, Hoover, Kneil, & Yaron, 2012;Stevens & Jaykus, 2004;Taskila et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that the extracts of fresh produce such as lettuce, perilla leaves and cucumber had no significant antimicrobial activity (30,51). In order to determine that the enzyme digestion had no significant effect on bacterial viability, controls were run with Salmonella confirming that the concentrations of pectinase and cellulase for digesting both lettuce and spinach had no significance effect (P>0.05) on the viability of Salmonella (Figure 4.1).…”
Section: The Effect Of Enzyme On the Viability Of Salmonellamentioning
confidence: 99%
“…However, there are some concerns that these methods may not be sufficient to detach all the bacteria from the produce. Inoculation studies have demonstrated that the recovery of bacteria using blending were lower than the original inoculation levels thus indicating that blending was not an efficient method (30,33).…”
Section: Introductionmentioning
confidence: 99%
“…Overview of Bacteriological Analytical Manual (FDA-BAM) worklow for the detection, isolation, and subtyping of Salmonella. It takes 5 days for the detection and isolation of Salmonella, and a week more for subsequent conirmation and subtyping recent molecular methods, such as MS, WGS, and PCR/qPCR, may shorten the result time [36].…”
Section: Culture-independent Methodsmentioning
confidence: 99%